THE CORRUPTION OF THE RULE OF LAW. Issue 2 (2018) - Hasnas, John
Abstract: The corruption of the rule of law is an ambiguous phrase. It can refer either to the corruption of the value of the rule of law or to the corrupting effect that the commitment to the rule of law produces. This essay explains how both can be the case. The rule of law is one of a cluster of values that liberal political theory requires a morally legitimate government to exemplify. Thus, the rule of law is a component part of a just political structure. However, the phrase "the rule of law" is often used colloquially to refer to most or all of the cluster of liberal values. When used in this way, a duty to obey the law often attaches itself to the concept of the rule of law. It is the association of this duty with the concept of the rule of law when used in its narrow, literal sense to refer to only one of the liberal values that corrupts both those who are committed to the rule of law and the respect for the value itself.